PERAN KEPALA MADRASAH DALAM MENINGKATKAN ETOS KERJA GURU - Pepilina, Dini; Maryati, Ulfa Dina (STIT AL MULTAZAM, 2022)
The purpose of this study was to determine the role of madrasah principals in improving teacher performance. The research uses a field research approach (field research). The results of the study showed that the head of the madrasah always carried out direct supervision or supervision by going around the class to see the teacher. In addition to supervising the teaching of the principal, the madrasah principal also plays a role in the process of monitoring or evaluating the work of all staff in the madrasa, including teachers, the madrasah principal tries to influence teachers and employees to inspire enthusiasm for work and commitment to task goals. The conclusion of this study is that the principal plays an active role in efforts to improve the work ethic of teachers, namely by establishing harmonious relationships with fellow teachers (teachers), providing welfare to adequate teachers, controlling and evaluating teachers in carrying out their duties so that they can change their mindset. in building teacher character, so that teachers participate in building madrasas to be at the forefront in accordance with their vision and mission.